METHODOLOGICAL ISSUES OF INCREASING INVESTMENT ACTIVITY OF COMMERCIAL BANKS (American Journal of Business Management, Economics and Banking, 2026)
This study comprehensively analyzes the methodological issues of increasing the investment activity of commercial banks. In particular, the issues of using modern financial instruments in the development of investment activities of banks, improving the risk management system and diversifying the investment portfolio are covered. The role of commercial banks in financing the real sector, mechanisms for supporting innovative projects and proposals aimed at improving the investment climate are developed.